Metabolic Responses of Meniscus to IL-1β - Cook, Alex E.; Cook, James L.; Stoker, Aaron M. (The Journal of Knee Surgery, 2018)
This article identifies the potential mechanisms of action for meniscal degeneration in response to joint inflammation and potential contributions of the meniscus to the development and progression of osteoarthritis (OA). It was hypothesized that interleukin-1β (IL-1β) stimulation of meniscal explants would result in significant increases in nitric oxide (NO), matrix metalloproteinase (MMP) production and activity, and relevant cytokine production compared with controls. Canine meniscal explants (4 mm) were cultured for 21 days with (IL-1) or without (negative control [NC]) 50 ng/mL rcIL-1β (n = 6/group). Media were changed every 3 days and analyzed for MMP activity, ADAMTS-4 activity, MMP-1, MMP-2, MMP-3, MMP-9, MMP-13, NO, prostaglandin E2 (PGE2), IL-6, IL-8, monocyte chemotactic protein-1 (MCP-1), and keratinocyte-derived chemokine (KC) concentrations. Media NO and PGE2 concentrations were significantly higher in the IL-1 group at all time points except for days 9 and 12. The concentrations of MMP-13 were significantly higher in the IL-1 group at days 3, 6, 9, and 12. The production of MMP-2 was significantly lower in the IL-1 group on days 3 through 15. ADAMTS4 activity was significantly higher in the IL-1 group on days 6 through 18. MMP-3 concentrations and general MMP activity were significantly higher in the IL-1 group at all time points. Concentrations of IL-6, IL-8, MCP-1, and KC were significantly higher in the IL-1 group at most time points. Glycosaminoglycans (GAG) content decreased significantly (p = 0.009) in the IL-1 group compared with the NC group. Proinflammatory mediators appear to directly influence degradative processes in the meniscus, which in turn contribute to development and progression of OA by production of proinflammatory and degradative mediators. These findings have important clinical implications for the management of the degenerative meniscus and the osteoarthritic knee.
Keywords: meniscus; inflammation; ex vivo; meniscal degeneration; osteoarthritis